Implementation of the Independent Learning Curriculum in Islamic Religious Education Subjects at MTs Negeri 2 Surakarta - hanani, umi; Rohmadi, Yusuf (JUPE : Jurnal Pendidikan Mandala, 2023)
The independent curriculum is a curriculum with intracurricular learning various kinds so that students can be more optimal and have concepts and strengthen them competence he has. This research aims to determine the implementation of the independent learning curriculum in Islamic religious education subjects. This research uses field research by collecting data through observation, interviews and documentation, and the validity of the data is tested using triangulation of sources and methods. The results of this research are that the implementation of the meedeka learning curriculum in Islamic religious education subjects is good, starting with carrying out diagnostic assessments related to readiness, students' interest in mapping, determining essential material, preparing systematic learning implementation plans, and the use of differentiated learning. i.e differentiation of content, process, product and environment. And the last one is carrying out evaluations such as providing motivation and assignments. Therefore, students can follow the learning process well because the learning model implemented has strong support from the school, this can be proven by the supporting facilities and infrastructure provided by the school.